Drug-release system of microchannel transport used in minimally invasive surgery for hemostasis - Huang H; Liu H; Zhou H; Liang Z; Song D; Zhang Y; Huang W; Zhao X; Wu B; Ye G; Huang Y (Dove Medical Press, 2019)
Hong Huang,1,* Houhe Liu,2,* Hua Zhou,1,* Zhiling Liang,2 Dandan Song,2 Yun Zhang,2 Wanqiu Huang,2 Xiaotian Zhao,2 Bo Wu,2 Guodong Ye,2 Yugang Huang2 1Key Laboratory for Major Obstetric Diseases of Guangdong Province, Department of Pharmacy, The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou 510150, China; 2Key Laboratory of Molecular Target and Clinical Pharmacology of Guangdong Province, School of Pharmaceutical Sciences, The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou 511436, China *These authors contributed equally to this work Background: Sucrose allyl ether (SAE) containing hemostatic drugs and a photoinitiator was established to treat mild postpartum hemorrhage or long-term continuous abnormal uterine bleeding in minimally invasive surgery (MIS) using a photopolymerization method. Methods and results: Real-time infrared spectroscopy and rheological experiments showed that the SAE monomer with shear-thinning characteristics could polymerize rapidly into a transparent membrane. Cytotoxicity experiments in vitro showed that this system could elicit a long-term hemostatic effect. Tissue adhesion was also evaluated. The photo-stability of four delivered antifibrinolytic drugs (6-aminocaproic acid, ethylenediaminediacetic acid, tranexamic acid and p-(aminomethyl) benzoic acid) was tested by ultraviolet-photolysis experiments and illustrated by time-dependent density functional theory. Sustained-release experiments revealed that the formed film could be used as a drug carrier. Molecular docking and molecular dynamics were done to investigate the binding mechanism between hemostatic drugs as ligands and the human plasminogen kringle-1 (1HPK) as a target. Conclusion: It has been suggested that SAE with tranexamic acid could be a drug-release system of microchannel transport used in MIS. This system could tackle the dilemma of fluidity and adhesion in MIS. The photo-stable tranexamic acid was the most suitable drug according to its satisfactory binding energy, good photo-stability, and sustained release. Keywords: hemostasis, photopolymerization, minimally invasive surgery, molecular simulation